2017
DOI: 10.1159/000475444
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin Inhibits Heat-Induced Apoptosis by Suppressing NADPH Oxidase 2 and Activating the Akt/mTOR Signaling Pathway in Bronchial Epithelial Cells

Abstract: Background: Heat causes bronchial epithelial cell apoptosis, which is a known factor contributing to airway damage during inhalation injury. Accumulating evidence has shown the effect of curcumin on inhibiting apoptosis. In this study, we investigated whether curcumin suppresses heat-induced apoptosis in bronchial epithelial cells and the underlying mechanism. Methods: Bronchial epithelial cell line 16HBE140 cells were incubated at either 42 °C, 47 °C, 52 °C, or 57 °C for 5 min in a cell incubator and then ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Unexpectedly, the effects of curcumin on TOR were diverse in different cells or animals. Our study was coincident with the study of curcumin on bronchial epithelial cells of rats (Peng et al., 2017). However, there are inconsistent reports that curcumin has the potential to inhibit TOR signalling in human bladder cancer cells (Tian et al., 2017), human gastric cancer cells (Li et al., 2017), mouse prostate cancer cells (Narayanan, Nargi, Randolph, & Narayanan, 2009) and mouse cardiomyocytes (Yang, Xu, Li, & Jiang, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Unexpectedly, the effects of curcumin on TOR were diverse in different cells or animals. Our study was coincident with the study of curcumin on bronchial epithelial cells of rats (Peng et al., 2017). However, there are inconsistent reports that curcumin has the potential to inhibit TOR signalling in human bladder cancer cells (Tian et al., 2017), human gastric cancer cells (Li et al., 2017), mouse prostate cancer cells (Narayanan, Nargi, Randolph, & Narayanan, 2009) and mouse cardiomyocytes (Yang, Xu, Li, & Jiang, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, TOR was found to activate S6 kinase 1 (S6K1) and depress eukaryotic initiation factor 4E‐binding protein 1 (4E‐BP1) in mammals (Nissim & Nahum, 2004). A previous study found that curcumin triggered the mTOR signalling pathway in the bronchial epithelial cells of rats (Peng, Pu, Tang, & Wu, 2017). However, no study has explored the relationship among curcumin, AAT, and PepT1, and the TOR signalling pathway, which requires further study.…”
Section: Introductionmentioning
confidence: 97%
“…ROS generation is known to be an important factor in tumor cell death [26, 27]. To further confirm the role of ROS on PD-mediated apoptosis, HeLa and C33A cells were treated with PD to elevate levels of intracellular ROS production (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to consider that these apparently contradictory findings may be related with the final concentration of CMC2.24 in vivo and within the macrophages in vitro. Other in vitro studies report contrasting effects of natural curcumin on production of ROS, depending on the cell type and concentration . In vivo, administration of natural curcumin has been shown to reduce oxidative stress by inhibiting NF‐kB signaling, which would also decrease the expression of various cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro studies report contrasting effects of natural curcumin on production of ROS, depending on the cell type and concentration. [37][38][39][40][41][42] In vivo, administration of natural curcumin has been shown to reduce oxidative stress by inhibiting NF-kB signaling, 43 which would also decrease the expression of various cytokines. In fact, our research group has recently shown that CMC2.24 inhibits NF-kB signaling.…”
Section: Discussionmentioning
confidence: 99%